Crisis Management Public Relations of PT KAI Commuter Jabodetabek on Handling KRL Cross Accident September 2015 - Dwi Putri Loven; Maylanny Christin; Ayub Ayub (Universitas Mataram, 2020)
This study titled “Crisis Management Public Relations of PT KAI Commuter Jabodetabek on Handling KRL Cross Accident September 2015” the problem of the research is the management crisis, crisis management strategy efforts to crisis, the role when crisis that is enforceable by the division of Public Relations PT KAI Commuter Jabodetabek (KCJ) in resolving the crisis accident of 2 KRL at Juanda Station. This research uses the Gonzales-Herero and Pratt crises method management who analogous a crisis like the stages of life.This research used qualitative case study research accompanied by descriptive exposure. The data was obtained through direct observation, interviews and literature studies, while the informants in this research was Assistant Communication Manager PT KCJ and Public Relations Manager of the Central Bank Republic of Indonesia West Java Province as the source triangulation.The results of this study shows that crisis management conducted by PT KCJ has been carried out starting from the victims evacuation, evacuation of the damaged wagon train, the recovery location of the accident, to the process of health settlement costs for the victims of accident. Keywords: Crisis Management, KRL Cross Accident, PT KAI Commuter Jabodetabek, Public Relations, Gonzales-Herero and Pratt Method